Pengaruh Lifestyle dan Brand Awareness terhadap Brand Loyalty dengan Brand Image sebagai Variabel Intervening Pada Mahasiswa FEB UNISMA Pengguna Sepatu Converse - Hariani, Isna; Rachma, N.; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract In Indonesia, Converse shoes occupy the highest position in the school shoe category in the Top Brand Award. A brand that occupies a top position can be sure that the brand has a good image in the eyes of consumers. This research aims to find out whether brand image is able to mediate the influence of lifestyle and brand awareness on brand loyalty among Converse shoe users. The type of research used is explanatory research with a quantitative approach. The research sample consisted of 100 FEB UNISMA students in the category of having bought Converse shoes at least twice. The data collection method was carried out by distributing questionnaires. Data analysis methods use validity tests, reliability tests, normality tests, path analysis, t tests, and Sobel tests. The research results show that Lifestyle and Brand Awareness have no significant effect on Brand Loyalty for Converse shoes through Brand Image. Keywords: converse, lifestyle, brand awareness, brand image, brand loyalty